A review of tutorial manual by Victoriia Ihnatenko “Teaching annotated and summary translation of scientific agrarian French articles to pre-service translators” - Л. В. Бондар (Іноземні мови, 2019)
This publication presents a review of the tutorial manual «Teaching annotated and summary translation of scientific agrarian French articles to pre-service translators» written by Doctor of Pedagogy Victoriia Ihnatenko for Ukrainian Bachelor students majoring in specialty 035 Philology. The structure and content of the reviewed work are analysed. The expediency of its use for building prospective translators’ competence in annotated and summary translation of scientific agrarian texts within the educational discipline “A practical course of French as a second foreign language and translation studies” taught to fourth-year university students is emphasised.